IDENTIFIKASI FAKTOR-FAKTOR PENENTU STRATEGI PEMASARAN DESA WISATA BANYUMULEK - Lalu Adi Permadi; Nur Aida Arifah Tara; G. A. Sri Oktariyani (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
This research is aimed to identify determinant factors of Banyumulek rural tourism marketing strategy. This research was qualitative research that used descriptive techniques and SWOT analysis as its tools. The participants chosen by a purposive sampling method. The data was collected by using observation, interview, documentation, and library study. The result of the research showed that there were 13 internal factors and 8 external factors which became the determinant factors of Banyumulek rural area marketing strategy. These factors were divided into nine Strengths, four Weaknesses, four Opportunities, and four Threats. The main Strength of the village was the ability of village craftsmen to produce traditional pottery. The prime weakness of the rural tourism area was low tourism facility. Meanwhile the Banyumulek village main opportunity was market opportunity at home and abroad; and the prime threat to the Banyumulek Tourism Village is the decrease in the use of earthenware products due to the fading of cultural customs and local wisdom values. Keywords: Rural; Tourism; Internal factors; External factors